'The program was the solution to the problem': Process evaluation of a multi-site driver licensing program in remote communities. (March 2017) - Cullen, Patricia; Chevalier, Anna; Hunter, Kate; Gadsden, Tom; Ivers, Rebecca
Abstract: Introduction: The low level of licenced drivers in remote Aboriginal communities in the Northern Territory (NT) Australia constitutes a risk factor for transport injury, high incarceration rates, and reduced ability to access employment and health services. The DriveSafe NT Remote program was implemented by the NT Government to increase driver licensing in remote communities. This evaluation reviews the program delivery, acceptability, implementation challenges and licensing outcomes. Methods: A mixed-methods approach was used, incorporating program observation and key informant perspectives ( n =30). Program data (collected April 2012 to June 2014) and de-identified licensing data from the NT Motor Vehicle Registry were analysed for trends in service delivery and licensing rates pre and post-program. Results: Interviewees reported strong support for the program, and regarded the program as highly engaging and acceptable. There was a greater increase in new licences at intervention sites (Learner 24% and Open licence 18%) compared with other remote areas (Learner licence 13% and Open licence 8%). There appeared to be a dose response relationship with greater licence outcomes at communities that received higher levels of program delivery. Discussion: DriveSafe NT Remote is a Government delivered program providing licensing services to Aboriginal clients in remote Northern Territory communities, and is increasing driver licensing rates. The flexible delivery and culturally responsive approach should lead to further positive licensing outcomes. Addressing barriers to licence participation faced by Aboriginal people is an innovative approach to reducing transport disadvantage and positively impacting health and well-being in remote communities. This evaluation demonstrates a pragmatic approach to assessing program implementation of a multi-site community-based program in a vulnerable and underserviced population; it is anticipated this approach could be applied to other settings to ensure programs responsively address road safety in Aboriginal populations. Highlights: Remote Aboriginal communities are diverse and vulnerable to transport disadvantage. Driver licensing was facilitated by a culturally-responsive and flexible approach. Licensing outcomes were greatest at sites receiving a high dose of program delivery. Multi-site community licensing programs require strong local support and engagement. Process evaluation of multi-site community programs are pragmatic and adaptable.